Teacher Human Resource Management in Fostering Students' Morals in Educational Institutions - Aziz, Irfan Maulana; Mutamimah, Duwi Habsari; Sustiawan, Asis (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze human resource management in fostering students' morals towards teachers in educational institutions. The background of this research is based on the importance of character education in building respect for students and the challenges of declining morals due to social and technological developments. The research uses a qualitative approach with a case study design carried out at Madrasah Ibtidaiyah Muhammadiyah (MIM) Ngreco, Tegalombo District, Pacitan Regency. The research subjects included school principals, teachers, education staff, students, and parents who were selected through purposive sampling techniques. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation, while data validity was tested through triangulation of sources and techniques, member checks, and trail audits. The results of the study show that human resource management in fostering students' morals is carried out through four main functions, namely planning, organizing, implementing, and supervising. Planning is carried out by integrating moral values in learning tools and religious habituation programs. Organizing is carried out through the division of tasks and collaboration between teachers in character development. The implementation is carried out through the example of teachers, habituation activities, and strengthening religious school culture. Supervision is carried out through continuous evaluation of student behavior and teacher performance in moral development. This study concludes that structured human resource management based on religious values is able to improve students' morals towards teachers and create harmonious relationships in the educational environment. These findings make a theoretical contribution to the development of character-based education management as well as practical implications for educational institutions in designing moral development programs in a systematic and sustainable manner.